A new species of Begonia Linn. (Begoniaceae) in karst regions from Guizhou, China - He, Shun-Zhi; Guo, Shi-Wei; Chen, Wen-Hong; Zhang, Rong-Mei; Shui, Yu-Min (Phytotaxa, 2019)
Karst regions provide a special environment for plant development, and have a highly endemic flora. A tuberous Begonia species, collected from a limestone mountain in Guizhou province, has been confirmed to be new to science, described and illustrated here. In sect. Diploclinium, the new species, Begonia zunyiensis S.Z.He & Y.M.Shui sp. nov., is similar to B. labordei H.Lév., but differs in having lanceolate leaves, fused filaments and styles, and the largest wing on the fruit being falciform.